Revenue Management Practices and their Impacts on Financial Performance of Star-Rated Hotels in Kenya - Murimi, Michael; Wadongo, Billy; Olielo, Tom (International Journal of Business Strategy and Social Sciences, 2021)
The study’s goal was to investigate how revenue management (RM) techniques affect the financial performance of Kenya’s star-rated hotels. The study aimed to examine if RM policies and implementation, the RM team, the application of RM methodologies, RM data and information, and the use of pricing and non-pricing instruments were all factors. The study used a cross-sectional survey research methodology and took a quantitative approach. The survey included 137 revenue managers from Kenyan all-star hotels. The structural equation modeling was used to test the linkages; revenue management strategies have an impact on hotel financial success, according to the research. The results indicated that RM practices explain variation in financial performance indicators by 42.7 percent (R2 =0.427), improved financial performance by 48.4 percent (R2 =0.48.4), and overall performance by 47.4 percent (R2 =0.474). The article recommends that hotels adopt RM tactics to fully achieve and maximize financial performance, including reducing operational expenses, forecasting hotel growth, improving yields, and generating income.